ANALISIS SIKAP PEDULI LINGKUNGAN DAN MINAT BERWIRAUSAHA MAHASISWA PADA PERKULIAHAN PENGETAHUAN LINGKUNGAN - Fahmy Armanda; Wulandari Saputri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Community in the 21st was faced with a number of challenges, one of which was environmental problems and how to survive in the 21st century. For this reason, there were two important things to be developed, namely an environmentally caring attitude and an interest in entrepreneurship. The development of both should be facilitated by lectures on Environmental Knowledge. This research is intended to analyze the environmental care attitude and interest in student entrepreneurship. The research method used was descriptive qualitative and data were collected through questionnaires and interviews. The results of this study are 1) The attitude of caring for the student's environment needs to be improved; 2) The interest in student entrepreneurship is very high so it needs to be facilitated through learning that invites students to practice the skills that have been taught. The results of this study are expected to be a foothold in how to develop learning to support the development of environmental awareness and interest in student entrepreneurship.